Economic activity of the organization of the service sector in the conditions of modern economy - M. V. Rybasova (Вестник Северо-Кавказского федерального университета)
The article studies the current state of service sector organizations and the mechanism to ensure the growth of economic activity. The article proposes methods of integral assessment of the economic activity of the organization of the service sector based on comparative analysis, grouping of data, a systematic approach. The author determined that the current situation on the market of goods and services in Russia is a big problem and at the same time an opportunity for growth and development. A general analysis of the activities of service sector organizations that operate in a constantly changing market economy is proposed. A brief overview of the key concepts of the service sector and the market economy is given. The analysis reveals the dependence of the service sector on political and economic phenomena in the country. As a branch of socio-economic activity, the service sector is an association of organizations, the purpose of their activities is to provide services to people. The increasing role of the service sector in the developing socio-economic system, which undergoes changes of various kinds in the process of increasing contradictions and disagreements in the conditions of resource constraints, is indicated. Based on the conducted research, it is concluded that over the past decades there has been a steady formation and dominant growth of the service sector in many national economies in comparison with production, as well as an increase in the contribution of the service sector to the formation of such a macroeconomic indicator as gross domestic product.